Critical Issues in the Development of Immunotoxins for Anticancer Therapy - Kim, Ji Sun; Jun, Sei Yong; Kim, Yong Sung (Journal of Pharmaceutical Sciences, 2020)
Immunotoxins (ITs) are attractive anticancer modalities aimed at cancer-specific delivery of highly potent cytotoxic protein toxins. An IT consists of a targeting domain (an antibody, cytokine, or another cell-binding protein) chemically conjugated or recombinantly fused to a highly cytotoxic payload (a bacterial and plant toxin or human cytotoxic protein). The mode of action of ITs is killing designated cancer cells through the effector function of toxins in the cytosol after cellular internalization via the targeted cell-specific receptor-mediated endocytosis. Although numerous ITs of diverse structures have been tested in the past decades, only 3 ITs—denileukin diftitox, tagraxofusp, and moxetumomab pasudotox—have been clinically approved for treating hematological cancers. No ITs against solid tumors have been approved for clinical use. In this review, we discuss critical research and development issues associated with ITs that limit their clinical success as well as strategies to overcome these obstacles. The issues include off-target and on-target toxicities, immunogenicity, human cytotoxic proteins, antigen target selection, cytosolic delivery efficacy, solid-tumor targeting, and developability. To realize the therapeutic promise of ITs, novel strategies for safe and effective cytosolic delivery into designated tumors, including solid tumors, are urgently needed.
Keywords: Animals; Antineoplastic Agents; Bacterial Toxins; Clinical Trials as Topic; Cytosol; Exotoxins; Humans; Immunotoxins; Neoplasms; Protein Binding; Protein Structure, Secondary; cytosolic delivery; cytotoxic protein; developability; immunoconjugate; immunogenicity; immunotoxin; off-target toxicity; toxins